Nutritional Value of Selected Edible Ficus Fruit in Kuantan - Nadira Nazua; Rozilawati Shahari; Che Nurul Aini Che Amri; Nur Shuhada Tajudin; Mohd. Radzali Mispan (Journal of Tropical Life Science, 2020)
Interest in the nutritional value content in food had been increasing as one of the ways to reduce the disease among the human being. Ficus is one of the fruit that contained high in major source of nutrients. Considering the important towards the mankind, this study was conducted to evaluate the nutritional content of Ficus fruit. There were six species and varieties of Ficus used in this study. The fresh sample was collected from selected area in Kuantan, Pahang. The major proximal components such as moisture content, crude fibre, crude lipid, total ash, crude protein, carbohydrate and energy was analysed using AOAC method. Based on this study, the moisture content ranges from 36. 33 % - 49.67 % in F. carica cv. BTM6; crude protein 2.3 % - 4.58 % in F. carica cv. TGF; crude lipid 0.01 % - 0.11 % in F. carica cv. BTM6; total ash 14.94 % - 21.22 % in F. carica cv. Alma and crude fiber 0.88 % - 3.36 % in F. carica cv. BTM6. The highest value of carbohydrate and energy content was found in F. hispida with 43.86 % and 175.44 kJ, respectively. According to our findings, consumption of Ficus fruit is recommended for commercialized in green industry based on its nutritional content that was crucial for human health.